PENGARUH STRATEGI PEMASARAN TERHADAP KEPUASAAN PELANGGAN DI CV MARTA JAYA - Didan Muhammad Faizal; Arga Sutrisna; Ari Arisman (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of marketing strategy on customer satisfaction at CV Marta Jaya which is used in this research method, namely using a quantitative research method using 100 respondents research and the research tool used in this study is simple linear regression using SPSS version 25. The results of this study indicate that marketing strategies can create consumer demand through customer satisfaction influenced by goods or services needed by customers, prices of goods or services, services, distributing goods or services and promotional activities